Optomagnonically induced RoF chaotic synchronization. (1st August 2022) - Gao, Yong-Pan; Liu, Xin-Chang; Cao, Cong; Han, Li-Hong; Lu, Peng-Fei
Abstract: Optomagnonics is a good platform for the interplay of radio frequency and optical signals, which are the primary communication carriers in the present day. On the basis of optomagnonics, we provide a multi-scale method for analyzing its behavior, including frequency comb and RoF chaotic synchronization at the microwave scale. Adjusting the pump light intensity permits the transition of RoF signals between harmonics, frequency combs, and chaotic movements. The dual optomagnonical device enables the synchronization of RoF signals between different cavities. Our study will contribute to the use of multiscale electromagnetic wave coupling in both conventional and quantum information applications.